Karakteristik Mikrobiologis Kombucha Dari Berbagai Jenis Olahan Teh - Yuli Febrianti; Reni Dwi Riastuti (Biogenesis: Jurnal Ilmiah Biologi, 2016)
This research aimed to analyze microbiological characteristics of kombucha from various types of tea processing which tasty to drink and gave benefits to examine some types of diseases. This research used an experimental method. The kombucha microbiology of old and new colonies were analyzed quantitatively descriptive by Levene homogeneity test, Kolmogorov-Smirnov normality test, and Shapiro-Wilk test. It was continued by Kruskal-Wallis and Mann-Whitney test. The results of data analysis were the average thickness, wet weight and diameter by using Kruskal-Wallis test that the provision of various types of processed tea was significantly different with the wet weight (0.222 < 0.05) but it was not significantly different to the thickness (0.170 > 0.05) and diameter (0.637 > 0.05) the old kombucha colony. Furthermore, Mann-Whitney test obtained was significant (p-value) > 0.05. It was showed that it was not significantly different to the average data wet weight of old kombucha colony. In addition, It was significantly different to various type of tea processing to the thickness (0.015 < 0.05) fresh weight (0.017 < 0.05), diameter (0.046 < 0.05), and the sheet (0.042 < 0.05) new kombucha colony. Furthermore, Mann-Whitney test obtained was significant (p-value) > 0.05. It means that it was not significantly effective to the average data of thickness, wet weight, diameter, sheet new kombucha colonies. The best treatment was administrating of green tea (P3) in the old and new kombucha colonies were significantly different from other treatments.